Myelomonocytic cell recruitment causes fatal CNS vascular injury during acute viral meningitis. - Kim, J; Kang, S; Dustin, M; McGavern, D (2009)
Lymphocytic choriomeningitis virus infection of the mouse central nervous system (CNS) elicits fatal immunopathology through blood-brain barrier breakdown and convulsive seizures. Although lymphocytic-choriomeningitis-virus-specific cytotoxic T lymphocytes (CTLs) are essential for disease, their mechanism of action is not known. To gain insights into disease pathogenesis, we observed the dynamics of immune cells in the meninges by two-photon microscopy. Here we report visualization of motile CTLs and massive secondary recruitment of pathogenic monocytes and neutrophils that were required for vascular leakage and acute lethality. CTLs expressed multiple chemoattractants capable of recruiting myelomonocytic cells. We conclude that a CD8(+) T-cell-dependent disorder can proceed in the absence of direct T-cell effector mechanisms and rely instead on CTL-recruited myelomonocytic cells.